Producción y purificación de β-N-acetilhexosaminidasa en cultivo sumergido de Lecanicillium lecanii inmovilizado en espuma de poliuretano - Carrasco Navarro, Ulises (Universidad Autónoma Metropolitana, 2011)
El objetivo del presente trabajo fue producir y purificar la enzima Nacetilhexosaminidasa (Nhasa) a partir de un cultivo sumergido del hongo Lecanicillium lecanii inmovilizado en espuma de poliuretano, para lo cual se utilizaron las condiciones reportadas por Carrasco y col. (2009) y se probaron dos protocolos de purificación. Inicialmente, se llevó a cabo la cinética de producción Nhasa, para lo que se utilizaron, como inóculo, biopartículas (hongo inmovilizado) en un biorreactor y como control se utilizaron esporas libres. Se encontró que la actividad volumétrica al utilizar biopartículas fue cuatro veces mayor (48.82±6.14 U/L), con respecto al control (11.2±0.26 U/L). De igual modo la mayor actividad específica se obtuvo al utilizar como inóculo las biopartículas obteniéndose 0.25±0.07 U/mg de proteína, mientras que, al inocular el reactor con esporas, solo fue de 0.028±0.0007 U/mg de proteína. En cuanto a la actividad Nhasa/g de sustratos sólidos iniciales (SSI), la mayor actividad se obtuvo en el cultivo con las biopartículas (2.73±0.34 U/gSSI) a diferencia del cultivo inoculado con esporas (0.62±0.014 U/gSSI). Posteriormente, se diseño una estrategia de purificación de una Nhasa a partir del extracto crudo enzimático obtenido del cultivo sumergido inoculado con biopartículas. Para tal fin, se precipitaron las proteínas con 40% de saturación con sulfato de amonio, obteniendo una actividad específica de 4.22±0.6 U/mg de proteína, el sobrenadante se llevo hasta 80% de saturación, obteniéndose en este segundo precipitado una actividad específica de 2±0.18 U/mg de proteína. Los precipitados de 40 y 80% fueron inyectados en una columna de exclusión molecular (Sephacryl™ S-100 High Resolution), separándose fracciones con actividades específicas de 7.92 U/mg y de 0.44 U/mg con factores de purificación de 2.55 y 0.14 para los precipitados al 40% y 80% de El objetivo del presente trabajo fue producir y purificar la enzima Nacetilhexosaminidasa (Nhasa) a partir de un cultivo sumergido del hongo Lecanicillium lecanii inmovilizado en espuma de poliuretano, para lo cual se utilizaron las condiciones reportadas por Carrasco y col. (2009) y se probaron dos protocolos de purificación. Inicialmente, se llevó a cabo la cinética de producción Nhasa, para lo que se utilizaron, como inóculo, biopartículas (hongo inmovilizado) en un biorreactor y como control se utilizaron esporas libres. Se encontró que la actividad volumétrica al utilizar biopartículas fue cuatro veces mayor (48.82±6.14 U/L), con respecto al control (11.2±0.26 U/L). De igual modo la mayor actividad específica se obtuvo al utilizar como inóculo las biopartículas obteniéndose 0.25±0.07 U/mg de proteína, mientras que, al inocular el reactor con esporas, solo fue de 0.028±0.0007 U/mg de proteína. En cuanto a la actividad Nhasa/g de sustratos sólidos iniciales (SSI), la mayor actividad se obtuvo en el cultivo con las biopartículas (2.73±0.34 U/gSSI) a diferencia del cultivo inoculado con esporas (0.62±0.014 U/gSSI). Posteriormente, se diseño una estrategia de purificación de una Nhasa a partir del extracto crudo enzimático obtenido del cultivo sumergido inoculado con biopartículas. Para tal fin, se precipitaron las proteínas con 40% de saturación con sulfato de amonio, obteniendo una actividad específica de 4.22±0.6 U/mg de proteína, el sobrenadante se llevo hasta 80% de saturación, obteniéndose en este segundo precipitado una actividad específica de 2±0.18 U/mg de proteína. Los precipitados de 40 y 80% fueron inyectados en una columna de exclusión molecular (Sephacryl™ S-100 High Resolution), separándose fracciones con actividades específicas de 7.92 U/mg y de 0.44 U/mg con factores de purificación de 2.55 y 0.14 para los precipitados al 40% y 80% de 6; The aim of this study was the production in submerged culture of the enzyme Nacetylhexosaminidase (Nhase) of the entomopathogenic fungus Lecanicillium lecanii immobilized in polyurethane foam and its purification. In a previous work, the conditions of immobilization and production were established (Carrasco et al., 2009), tested two purification protocols Initially kinetics of Nhase activity were carried out in a bioreactor using bioparticles and spores (free cells) as inocula, the former yields a maximum volumetric activity of 48.82± 6.14 U/L, whereas the latter was 11.2 ± 0.26 U/L i.e. more than fourfold the activity with bioparticules. The highest specific activity was also found when the bioparticles was used as inoculum (0.25±0.07 U/mg protein). Indeed, the highest Nhase/g of initial solid substrates (SSI) activity was determined in the culture using bioparticles (2.73 ± 0.34 U/gSSI), compared with the culture inoculated with spores (0.62 ± 0.014 U/gSSI). Purification of Nhase from crude enzymatic extract of submerged culture with bioparticles was carried out. Proteins were salted out at 40% saturation with ammonium sulfate obtaining a specific activity of 4.22 ± 0.6 U/mg, the supernatant was brought to 80% saturation with ammonium sulfate (2±0.18 U/mg). Each of these fractions were injected into a size exclusion chromatography column (Sephacryl™ S-100 High Resolution), obtaining specific activities of 7.92 U/mg and 0.44 U/mg with purification factor of 2.55 and 0.14 for the fraction precipitated at 40 and 80% saturation, respectively. Subsequently, the fractions with activity were subjected to ion exchange chromatography (Macro-Prep High Q support), nevertheless there was not a good separation and above all the enzymatic activity was absent. Based on the above, the purification protocol was modified, Nhase activities were determined as 88.2±10.78 Nhase U/mg protein, 16.58±2.26 U/mg The aim of this study was the production in submerged culture of the enzyme Nacetylhexosaminidase (Nhase) of the entomopathogenic fungus Lecanicillium lecanii immobilized in polyurethane foam and its purification. In a previous work, the conditions of immobilization and production were established (Carrasco et al., 2009), tested two purification protocols Initially kinetics of Nhase activity were carried out in a bioreactor using bioparticles and spores (free cells) as inocula, the former yields a maximum volumetric activity of 48.82± 6.14 U/L, whereas the latter was 11.2 ± 0.26 U/L i.e. more than fourfold the activity with bioparticules. The highest specific activity was also found when the bioparticles was used as inoculum (0.25±0.07 U/mg protein). Indeed, the highest Nhase/g of initial solid substrates (SSI) activity was determined in the culture using bioparticles (2.73 ± 0.34 U/gSSI), compared with the culture inoculated with spores (0.62 ± 0.014 U/gSSI). Purification of Nhase from crude enzymatic extract of submerged culture with bioparticles was carried out. Proteins were salted out at 40% saturation with ammonium sulfate obtaining a specific activity of 4.22 ± 0.6 U/mg, the supernatant was brought to 80% saturation with ammonium sulfate (2±0.18 U/mg). Each of these fractions were injected into a size exclusion chromatography column (Sephacryl™ S-100 High Resolution), obtaining specific activities of 7.92 U/mg and 0.44 U/mg with purification factor of 2.55 and 0.14 for the fraction precipitated at 40 and 80% saturation, respectively. Subsequently, the fractions with activity were subjected to ion exchange chromatography (Macro-Prep High Q support), nevertheless there was not a good separation and above all the enzymatic activity was absent. Based on the above, the purification protocol was modified, Nhase activities were determined as 88.2±10.78 Nhase U/mg protein, 16.58±2.26 U/mg nd 1.69±0.3 U/mg for precipitates of 40, 60 and 80% of saturation with ammonium sulfate, respectively. The accumulated enzyme activity in the precipitates with ammonium sulfate among 60 and 80% did not show significant differences, thus for the further work it was employed 60% saturation. Precipitated fraction was dissolved in Tris-HCl 50mM, NaCl 0.15M buffer pH 7.8 and ultrafiltrate (molecular weight cut off 10 KDa). The retentate was mixed up with 4% (v/v) Triton X-100 and 10% (v/v) acetonitrile and injected into size exclusion chromatography column (Sephacryl™ S-100 High Resolution). The fractions with activity were 10 (0.88 U/mg U/mg protein) and 11 (1.98 U/mg U/mg), with a purification factor of 72.12 and 162.16, respectively. Fractions 10 and 11 were injected in an ion exchange column (DEAE-Sepharose fast-flow). Fractions with Nhase activity were subjected to SDS-PAGE, showing only two bands between 50-75 KDa for fractions 20-30, fractions 31-33 observed a single band for the fraction 10 and also a single band in fractions 30-36 for the fraction 11. The purification of Nhase from a crude enzymatic extract of the immobilized Lecanicilliun lecanii was achieved after only three steps of purification. The purified Nhase is most active at pH 40°C and 6.0